Cost-effectiveness of vaccination with a quadrivalent HPV vaccine in Germany using a dynamic transmission model - Deniz Schobert; Vanessa Remy; Oliver Schoeffski (Health Economics Review, 2012)
Introduction: Persistent infections with human papillomavirus (HPV) are a necessary cause of cervical cancer and are responsible for important morbidity in men and women. Since 2007, HPV vaccination has been recommended and funded for all girls aged 12 to 17 in Germany. A previously published cost-effectiveness analysis, using a static model, showed that a quadrivalent HPV vaccination programme for 12-year-old girls in Germany would be cost effective. Here we present the results from a dynamic transmission model that can be used to evaluate the impact and cost-effectiveness of different vaccination schemas. Methods: We adapted a HPV dynamic transmission model, which has been used in other countries, to the German context. The model was used to compare a cervical cancer screening only strategy with a strategy of combining vaccination of females aged 12-17 years old and cervical cancer screening, based on the current recommendations in Germany. In addition, the impact of increasing vaccination coverage in this cohort of females aged 12-17 years old was evaluated in sensitivity analysis. Results: The results from this analysis show that the current quadrivalent HPV vaccination programme of females ages 12 to 17 in Germany is cost-effective with an ICER of 5,525/QALY (quality adjusted life year). The incremental cost-effectiveness ratio (ICER) increased to 10,293/QALY when the vaccine effects on HPV6/11 diseases were excluded. At steady state, the model predicted that vaccinating girls aged 12 to 17 could reduce the number of HPV 6/11/16/18-related cervical cancers by 65% and genital warts among women and men by 70% and 48%, respectively. The impact on HPV-related disease incidence and costs avoided would occur relatively soon after initiating the vaccine programme, with much of the early impact being due to the prevention of HPV6/11-related genital warts. Conclusions: These results show that the current quadrivalent HPV vaccination and cervical cancer screening programmes in Germany will substantially reduce the incidence of cervical cancer, cervical intraepithelial neoplasia (CIN) and genital warts. The evaluated vaccination strategies were all found to be cost-effective. Future analyses should include more HPV-related diseases.
Keywords: 330; cervical cancer; cervical intraepithelial neoplasia; genital warts; human papillomavirus; quadrivalent HPV vaccine; cost-effectiveness analysis; dynamic transmission model